K+ channelepsy: progress in the neurobiology of potassium channels and epilepsy - D'Adamo, Maria C.; Catacuzzeno, Luigi; Di Giovanni, Giuseppe; Franciolini, Fabio; Pessia, Mauro (Frontiers in Cellular Neuroscience, 2013)
K+ channels are important determinants of seizure susceptibility. These membrane proteins, encoded by more than 70 genes, make the largest group of ion channels that fine-tune the electrical activity of neuronal and non-neuronal cells in the brain. Their ubiquity and extremely high genetic and functional diversity, unmatched by any other ion channel type, place K+ channels as primary targets of genetic variations or perturbations in K+-dependent homeostasis, even in the absence of a primary channel defect. It is therefore not surprising that numerous inherited or acquired K+ channels dysfunctions have been associated with several neurologic syndromes, including epilepsy, which often generate confusion in the classification of the associated diseases. Therefore, we propose to name the K+ channels defects underlying distinct epilepsies as “K+ channelepsies”, and introduce a new nomenclature (e.g. Kx.y-channelepsy), following the widely used K+ channel classification, which could be also adopted to easily identify other channelopathies involving Na+ (e.g. Navx.y-phenotype), Ca2+ (e.g. Cavx.y-phenotype), and Cl- channels. Furthermore, we discuss novel genetic defects in K+ channels and associated proteins that underlie distinct epileptic phenotypes in humans, and analyze critically the recent progress in the neurobiology of this disease that has also been provided by investigations on valuable animal models of epilepsy. The abundant and varied lines of evidence discussed here strongly foster assessments for variations in genes encoding for K+ channels and associated proteins in patients with idiopathic epilepsy, provide new avenues for future investigations, and highlight these proteins as critical pharmacological targets.